2001
DOI: 10.1302/0301-620x.83b7.10102
|View full text |Cite
|
Sign up to set email alerts
|

Increased chromosome translocations and aneuploidy in peripheral blood lymphocytes of patients having revision arthroplasty of the hip

Abstract: The long-term biological effects of wear debris are unknown. We have investigated whether there is any evidence of cumulative mutagenic damage in peripheral blood lymphocytes of patients undergoing revision arthroplasty of predominantly metal-on-plastic total hip replacements compared with those at primary arthroplasty. There was a threefold increase in aneuploidy and a twofold increase in chromosomal translocations which could not be explained by the confounding variables of smoking, gender, age and diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(19 citation statements)
references
References 26 publications
(24 reference statements)
1
17
0
1
Order By: Relevance
“…In vitro studies have clearly demonstrated that cobalt particles can be highly cytotoxic when produced in high enough concentrations (Merritt and Brown 1993). There is also much concern about the effect of long-term exposure and the potential for chromosomal aberrations in the patient, as well as the risk of passing chromosomal abnormalities to the next generation (Case et al 1996, Doherty et al 2001, Ladon et al 2004, Bordner et al 2004a, Papageorgiou et al 2007, Ziaee et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have clearly demonstrated that cobalt particles can be highly cytotoxic when produced in high enough concentrations (Merritt and Brown 1993). There is also much concern about the effect of long-term exposure and the potential for chromosomal aberrations in the patient, as well as the risk of passing chromosomal abnormalities to the next generation (Case et al 1996, Doherty et al 2001, Ladon et al 2004, Bordner et al 2004a, Papageorgiou et al 2007, Ziaee et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow adjacent to the worn implant was found to show an increased number of chromatid breaks and gaps (Case et al 1996). At revision THA, patients with mixed types of CoCr prostheses had a 2.5-fold increase in peripheral blood lymphocytes with aneuploidy and 3.5 fold more chromosomal translocations than at primary THA (Doherty et al 2001). Wear debris from worn hip and knee prostheses in human tissue cultures has been found to damage chromosomes in a dose-dependent manner, which was specific to the type of metal.…”
Section: Introductionmentioning
confidence: 96%
“…These can lead to pain and removal of the implant. Metal ions in the blood have been shown to change the genetics in some blood cells, 23 although it has been shown that patients with metal-on-metal implants do not have an increased risk of developing cancer compared with the general population. 24 Metal ions can also cross the placenta and be absorbed by a fetus, so metal-on-metal implants are not recommended in women of childbearing age.…”
Section: Metal-on-metalmentioning
confidence: 99%